2019
DOI: 10.1042/bcj20190038
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of structure, function and inhibitor binding in UNC-51-like kinase 1 and 2 (ULK1/2)

Abstract: Autophagy is essential for cellular homeostasis and when deregulated this survival mechanism has been associated with disease development. Inhibition of autophagy initiation by inhibiting the kinase ULK1 (Unc-51-like autophagy activating kinase 1) has been proposed as a potential cancer therapy. While inhibitors and crystal structures of ULK1 have been reported, little is known about the other closely related kinase ULK2 (Unc-51-like autophagy activating kinase 2). Here, we present the crystal structure of ULK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 70 publications
3
57
0
Order By: Relevance
“…Using a dimensionality reduction approach based on Principal Component Analysis (PCA), we compared the sampling [103] achieved with the two force fields ( Figure 3A) and we identified a good overlap, suggesting that the two simulations give a consistent view on the ULK1 dynamics. We also evaluated the principal motions described by the first PC (Figure 3B-C) and we noticed that there is concerted motion between the loop 148-158 and a part of the activation loop (172-183), along with the loop adjacent to the catalytic lysine (in the region [35][36][37][38][39][40][41]. The two disordered regions 148-158 and 172-183 feature closing motions toward the rest of the ULK1 structure.…”
Section: Ulk1 Microsecond Dynamicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using a dimensionality reduction approach based on Principal Component Analysis (PCA), we compared the sampling [103] achieved with the two force fields ( Figure 3A) and we identified a good overlap, suggesting that the two simulations give a consistent view on the ULK1 dynamics. We also evaluated the principal motions described by the first PC (Figure 3B-C) and we noticed that there is concerted motion between the loop 148-158 and a part of the activation loop (172-183), along with the loop adjacent to the catalytic lysine (in the region [35][36][37][38][39][40][41]. The two disordered regions 148-158 and 172-183 feature closing motions toward the rest of the ULK1 structure.…”
Section: Ulk1 Microsecond Dynamicsmentioning
confidence: 98%
“…It could thus be expected that these mutations could impair its functional dynamics. In addition, the regulatory spine residue L78 and F81 in the proximity of the other disordered loop (35)(36)(37)(38)(39)(40)(41) also involved in the concerted conformational changes are also mutation sites. In particular, PSN approaches can also be used to infer functionally-damaging sites if the paths of communication between the mutation sites and other important functional sites for the kinase activity are taken into account.…”
Section: Assessment Of the Impact Of Mutations On Ulk1 Functionmentioning
confidence: 99%
“…Although this inhibitor is a potent ULK1 inhibitor, it has off-target liabilities including FAK. A recent structure-based study revealed that many compounds that would inhibit ULK1 would likely inhibit ULK2 and Aurora kinase as well (142). A more recently developed ULK1 inhibitor, ULK101, with increased specificity has been reported (143).…”
Section: Ulk1 Inhibitorsmentioning
confidence: 99%
“…The structure of ULK4 PD revealed the canonical bilobal domain architecture of protein kinases (PDB-ID 6TSZ, Figure 1C) that was similar to a recent ULK4 structure in complex with an inhibitor (pdb-code: 6U5L) (Khamrui et al, 2020) but a larger portion of the activation segment was visible in the ATP complex. The structures of the active ULK family members ULK1 and ULK2 superimposed well with ULK4 PD despite the low sequence identity (29%) shared between these two kinases (Chaikuad et al, 2019;Lazarus et al, 2015) (Figure 1D, Supplemental Figure S2).…”
Section: Structural Features Of the Ulk4 Pseudokinase Domainmentioning
confidence: 87%